Feasibility and acceptability of aquatic exercise therapy in burn patients - A pilot study - S.J.M. Sizoo; M. Akkerman; N. Trommel; J.J.P.H. Esser; M. Veen-van der Velden; I.M.M.H. Oen; C.H. van der Vlies; M.E. van Baar; M.K. Nieuwenhuis (Elsevier, 2021)
Background: As the assistive and resistive properties of water can facilitate the performance of exercise, aquatic exercise therapy might be a promising rehabilitation modality for burn patients. This study aimed to investigate the feasibility and acceptability of aquatic exercise therapy in adult burn patients with an indication for supervised exercise therapy. Methods: Eligible for this observational pilot study were all competent adult burn patients with an indication for supervised exercise therapy who had been admitted to the burn centre of the Maasstad Hospital between June 2016 and February 2017. Patients were asked to participate in an in-hospital aquatic exercise therapy program for a minimum of 2 weeks, 2 times per week, or otherwise serve as control by having land-based exercise therapy (regular care). Feasibility of aquatic exercise therapy was assessed by comparing the number of eligible patients to the number of patients that could actually participate, monitoring attendance rates, monitoring complications, and evaluating early experiences. Acceptability was assessed using the Water Exercise Acceptability Questionnaire. Results: Eleven patients were invited and ten of them agreed to participate. All chose aquatic instead of land-based exercise therapy. Participants were aged between 19 and 64 years and their burns affected 18-53% of total body surface area (TBSA). Aquatic exercise therapy appeared feasible in nine of 13 eligible patients (69%). Attendance rates were high (42-100%) and the majority of participants (n = 9) continued with aquatic exercise therapy beyond the initial two weeks. No serious complications (e.g. infections) occurred. Adverse symptoms (wound healing issues) were reported in five participants, but in four of them these were not likely to be due to the aquatic exercise therapy. Enjoyment was high and adherence to the aquatic exercise therapy was further facilitated by support from staff, a sense of achievement, noticeable improvements, personal motivation, and support from other participants. Peer support was reported as a positive side effect. Conclusions: These preliminary results indicate that aquatic exercise therapy is both feasible and acceptable for the majority of adult burn patients with an indication for supervised exercise therapy. No indications were found for an increased risk of infection or other serious complications.